Investment Commitments in South Asia Remained at a Peak Level in 2007 - Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
Investment commitments to infrastructure projects with private participation in South Asia amounted to almost US$29 billion in 2007, remaining in the US$28-29 billion range for the second consecutive year, according to just-released data from the private participation in infrastructure project database. With this investment level, South Asia accounted for 18 percent of the year's total investment commitments in developing countries. The high level of investment commitments was driven both by new projects and by projects implemented in previous years. The 58 new projects accounted for US$15.7 billion, while projects reaching financial closure in 1990-2006 attracted US$13.3 billion. Commitments to physical assets, remaining in the US$27-28 billion range, accounted for almost all the investment in the region in 2007. Payments to the government (such as spectrum or concession fees and divestiture revenues) amounted to US$0.6 billion, or less than 2 percent of annual investment.